2022
DOI: 10.1007/s10530-022-02746-1
|View full text |Cite
|
Sign up to set email alerts
|

Introduced predators and nest competitors shape distribution and breeding performance of seabirds: feral pigeons as a new threat

Abstract: Petrels are particularly sensitive to predation by introduced species. Many populations have reduced their breeding ranges, currently mainly occupying predator-free sites. Breeding range reduction leads to interspecific competition for nesting sites, which can be detrimental to petrels. Here, we evaluate how the presence of introduced mammals (cats Felis catus and rats Rattus spp.) and potential competitors for nest sites (Cory’s shearwaters Calonectris borealis and feral rock pigeons Columba livia) shape the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Large interannual coastal strandings of seabirds (alive and/or dead) have been reported worldwide (Bugoni et of long-lived, pelagic species that spend most of their life cycle at sea (Stidworthy and Denk 2018). Due to these particular life history traits, procellariforms are amongst the most endangered threatened taxonomic groups (Croxall et al 2012), considered highly sensitive to anthropogenic activities (e.g., fisheries interaction, habitat degradation, climate change, invasive and non-native species) (Tavares et al 2019;Rodríguez et al 2022). Therefore, data on the infectious agents affecting Procellariiformes is pivotal for the conservation of this group.…”
Section: Discussionmentioning
confidence: 99%
“…Large interannual coastal strandings of seabirds (alive and/or dead) have been reported worldwide (Bugoni et of long-lived, pelagic species that spend most of their life cycle at sea (Stidworthy and Denk 2018). Due to these particular life history traits, procellariforms are amongst the most endangered threatened taxonomic groups (Croxall et al 2012), considered highly sensitive to anthropogenic activities (e.g., fisheries interaction, habitat degradation, climate change, invasive and non-native species) (Tavares et al 2019;Rodríguez et al 2022). Therefore, data on the infectious agents affecting Procellariiformes is pivotal for the conservation of this group.…”
Section: Discussionmentioning
confidence: 99%
“…Free‐ranging insular cat populations are especially detrimental for seabirds (Dias et al, 2019; Medina et al, 2011; Nagata et al, 2022; Oliveira et al, 2022). A recent study by Rodríguez et al (2022) found that predation by cats and rats has shaped the current breeding distribution of petrel colonies in the Canary Islands, relegating them to isolated predator‐free areas. Similar findings have been reported in numerous other studies (e.g., Hervías et al, 2014), and likely explain the restricted breeding range of Manx shearwater in Madeira.…”
Section: Discussionmentioning
confidence: 99%